Desenvolvimento analítico, estudos de permeação cutânea e potencial de irritação ocular de formulações de repelentes à base de N',N'-dietil-m-toluamida - Santos, Juliana dos (2019)
N ', N'-diethyl-m-toluamide (DEET) is the most commonly repellent used against mosquito vectors of diseases such as dengue, yellow fever and chikungunya. In Brazil, DEET is found on the market in aerosol, solution, lotion and gel forms, in concentrations ranging from 6.65 to 25%. Until 2015, the pharmacopoeial method for DEET assay in bulk and solution used infrared spectroscopy, a technique little used for this purpose. In 2016 edition, this method was changed to an HPLC method. However, there is no pharmacopoeial method for the other forms. Despite the long time in the market, comparative studies on the penetration/permeation of different forms are not available, as well as studies of ocular irritation by alternative methods. In this scenario, the objective of this work was to validate an HPLC-UV method for the DEET assay in lotion, gel and solution, to evaluate the effect of the composition of the formulation on the penetration/permeation of the substance through the skin layers, and finally assess the potential for ocular irritation of formulations containing this substance available on the market by the alternative method HET-CAM. The analytical method was developed in Shimadzu chromatographic system, equipped with PDA detector, using C18 stationary phase, mobile phase composed of methanol, acetonitrile and water pH 4.5, flow rate of 1.0 mL min-1 and detection at 270 nm. The method specificity was confirmed by forced degradation tests, since in all the stress conditions used the DEET peak purity was index appropriate and good resolution between the peaks was observed. The method was linear in the range studied (2.5-100 μg mL-1) and showed good precision, since the DPRs in the two levels studied (repeatability and intermediate accuracy) were <2%. The average recovery for accuracy was within the recommended value (98-102%). Robustness was confirmed by factorial design 23, because none of the single factors or the combination of them significantly affected the DEET assay (p> 0.05). Considering the administration route, the photostability of DEET was studied under UVC radiation. The DEET presented good photostability and it was observed zero order kinetic in the experimental conditions. The skin penetration/permeation study was performed on Franz type cells using porcine skin as a membrane and phosphate buffer pH 7.4 with 0.5% polysorbate 80 as the receptor medium. All formulations were able to cross through the skin layers, reaching the receptor medium. The amount of DEET permeated was dependent of the formulation, being lotion > gel > solution (p<0.05). For the evaluation of ocular irritation potential, seven samples of DEET-based repellents were used and most of them were classified as "very irritant" or "irritant".